Weaving harmony from the classroom: A religious moderation-based classical guidance module as a preventive strategy against toxic positivity in elementary schools - Hadiarni; Rafsel Tas’adi; Wenda Asmita; Yosi Lestia (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Toxic positivity, the pressure to always think positively and deny negative emotions, is now emerging even in elementary school-aged children. This phenomenon may hinder emotional health and communication openness. This study aims to develop a classical guidance module grounded in religious moderation to reduce toxic positivity among elementary students. This study uses a 4-D model development research approach (Define, Design, Develop, Disseminate). However, this research only reached the development stage. The study was conducted at SDN 01 Lima Kaum, Tanah Datar, with a sample of 39 students from the fifth and sixth grades, selected using purposive sampling. Data were collected through questionnaires and interviews and were subsequently analysed descriptively and quantitatively. The results showed that 51% of students experienced toxic positivity in the high to very high category. The developed module was validated by experts, achieving a validity score of 76% (categorised as